Stereotactic radiotherapy in oligoprogressive and oligorecurrent urothelial cancer patients: A retrospective experience. (2019) - Francolini, G.; Desideri, I.; Detti, B.; Di Cataldo, V.; Masi, L.; Caramia, G.; Visani, L.; Terziani, F.; Muntoni, C.; Lo Russo, M.; Loi, M.; Livi, L.
Abstract: Urothelial cancer is one of the most common malignancies; after relapse or disease progression available therapeutic options are limited. We analyze efficacy and toxicity of local treatment on metastases using stereotactic body radiation therapy (SBRT) in selected patients with oligometastatic disease from urothelial cancer. A significant percentage of treated lesions achieved local control, with a promising overall response rate. Objectives: to analyze efficacy and toxicity of local treatment on metastases using stereotactic body radiation therapy (SBRT) in selected patients with oligometastatic disease from urothelial cancer. Materials and methods: Data from clinical records of 19 patients treated in our institution since May 2011 to October 2017 with SBRT for oligometastatic/oligoprogressive urothelial carcinoma were retrospectively collected. Clinical outcomes in terms of local control (LC), response rate, symptoms control, progression free and overall survival (PFS and OS), and adverse events were analyzed and reported. Results: Nineteen patients were treated on 25 metastatic lesions; 5 of them received treatment on multiple sites. After an average follow up of 11.5 months, LC was achieved in 17 lesions (68%) and there was no local recurrence in lesions with complete or partial response. OS was 13.8 months. Adverse events were reported only in 3 patients (5 overall events). No late toxicity was reported. Conclusions: An approach consisting in SBRT for local treatment of oligometastatic or persistent disease can be effective and safe in selected patients. Prospective studies are needed, to find correct selection criteria and optimal dose and fractionation.